Automated reference validation for scholarly publications using NLP - Khan, A S M Nasim; Khan, Mohammad Nasif Sadique; Howlader, MD. Adnan; Roy, Ayan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.